2021
DOI: 10.1088/1755-1315/824/1/012082
|View full text |Cite
|
Sign up to set email alerts
|

The effect of screen materials on the microclimate and growth of chili pepper plant

Abstract: Climate change often causes failure in cultivation. So, microclimate modification is needed. One of which is to use the screen to ensure the cultivation of chili pepper plants. The purposes of this study were to understand the effect of several types of screen materials on the growth of the chili pepper plant and to determine the best screen material for chili pepper plant cultivation. This study consisted of four treatments; there is no screen (NO), UV plastic screen with 0.6 mm (UV) of thickness, shading net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…(Nagy et al, 2017a) and total dry weight of chili were observed under the 25% shading (Table 6) (Stamps, 2009). Chili pepper plants' yields tended to decrease under a shade cloth with 50% light exclusion (Sumiyati et al, 2021). Plants under severe temperature stress will exhibit instabilities in their reduced fruit sizes, a decline in pollen viability, a faster rate of flowering, and shorter plants (Rosmaina et al, 2021).…”
Section: Parameters Studied Influences Referencesmentioning
confidence: 99%
“…(Nagy et al, 2017a) and total dry weight of chili were observed under the 25% shading (Table 6) (Stamps, 2009). Chili pepper plants' yields tended to decrease under a shade cloth with 50% light exclusion (Sumiyati et al, 2021). Plants under severe temperature stress will exhibit instabilities in their reduced fruit sizes, a decline in pollen viability, a faster rate of flowering, and shorter plants (Rosmaina et al, 2021).…”
Section: Parameters Studied Influences Referencesmentioning
confidence: 99%